2001
DOI: 10.1359/jbmr.2001.16.11.2126
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate Reduces Periprosthetic Bone Loss After Uncemented Primary Total Hip Arthroplasty: A Prospective Randomized Study

Abstract: Periprosthetic bone loss, especially in the proximal part of the femur, is common after cemented and uncemented total hip arthroplasty (THA). Bone loss can be progressive and, in the extreme, may threaten survival of the prosthesis. To study whether alendronate therapy can reduce bone loss adjacent to prostheses, 13 uncemented primary THA patients were randomized to the study. They received 10 mg alendronate ؉ 500 mg calcium (n ‫؍‬ 8) or 500 mg calcium only (n ‫؍‬ 5) daily for 6 months follow-up after THA. Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 29 publications
3
76
0
3
Order By: Relevance
“…These compounds have strong affinity to bone and can inhibit bone resorption [10]. Several clinical studies suggest the use of bisphosphonates as oral and local adjuvants in total joint arthroplasties increase periimplant bone density or reduce implant migration [19,26,27]. The effect of soaking morselized allograft in bisphosphonate before impacting it around an experimental implant has been described [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have strong affinity to bone and can inhibit bone resorption [10]. Several clinical studies suggest the use of bisphosphonates as oral and local adjuvants in total joint arthroplasties increase periimplant bone density or reduce implant migration [19,26,27]. The effect of soaking morselized allograft in bisphosphonate before impacting it around an experimental implant has been described [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, when administered orally, the bioavailability of bisphosphonate is generally very low, and its local delivery can be further delayed in regions of the skeleton with low blood perfusion, for example the femoral neck. Recent clinical studies have shown that systemic bisphosphonate treatment following prosthesis implantation reduced periprosthetic bone loss only after 3 months (Nehme et al, 2003;Venesmaa et al, 2001b), while significant bone loss arises during this initial period of 3 months (Venesmaa et al, 2001a). A solution to accelerate the local availability of bisphosphonate at the implant location is to deliver the drug locally.…”
Section: Introductionmentioning
confidence: 99%
“…These are all factors that may improve implant survival , Peter et al, 2005, Eberhardt et al, 2006. Although findings are conflicting, many RCTs have reported beneficial effects of bisphosphonates on periprosthetic bone mineral density and decreased stress shielding after primary THA (Yamaguchi et al, 2003, Yamasaki et al, 2007, Venesmaa et al, 2001, Fokter et al, 2005, Arabmotlagh et al, 2006. This increase in bone mineral density may even persist years after discontinuation of bisphosphonates treatment (Arabmotlagh et al, 2006).…”
Section: Study Iii: Bisphosphonatesmentioning
confidence: 99%
“…Although findings are conflicting, many clinical randomized trials have reported beneficial effects of short-term treatment with bisphosphonates on periprosthetic bone mineral density and deceased stress shielding after primary THA (Yamaguchi et al, 2003, Yamasaki et al, 2007, Venesmaa et al, 2001, Fokter et al, 2005, Arabmotlagh et al, 2006. Improved fixation of the implants due to bisphosphonates has therefore been suggested.…”
Section: Study III (Bisphosphonate Study)mentioning
confidence: 99%